2005
DOI: 10.1007/s11255-004-2312-0
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Peritoneal Dialysis: A Case Report and Review of Adequacy and Outcomes

Abstract: A case of pregnancy in a 27-year-old woman on peritoneal dialysis is presented. The case report is a detailed description of her course including changes in her peritoneal dialysis regimen and the use of continuous cycling to maximize dialysis adequacy while addressing the patient's recurrent abdominal pain and fullness. Also described is the management of complications including hypertension, gestational diabetes, and premature rupture of membranes. The discussion reviews the diagnosis of pregnancy, factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
21
0
5
Order By: Relevance
“…Some of these issues were encountered in our group of patients but did not prove detrimental to the pregnancy outcomes. The literature suggests that peritonitis can be successfully treated in pregnancy, 2,7,9,11,14 as was seen in our patients. In all cases, the peritoneal catheter insertions were performed in the second trimester to minimize risk of premature labour.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Some of these issues were encountered in our group of patients but did not prove detrimental to the pregnancy outcomes. The literature suggests that peritonitis can be successfully treated in pregnancy, 2,7,9,11,14 as was seen in our patients. In all cases, the peritoneal catheter insertions were performed in the second trimester to minimize risk of premature labour.…”
Section: Discussionsupporting
confidence: 68%
“…6,7 More recent reports suggest that pregnancy can be successfully completed with either haemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD) support. 2,[6][7][8][9][10][11] The decisions about timing for commencement and modality of dialysis are based on individual case reports or experience.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the Kt/V for PD patients should be increased to the range of 2.2–2.4 for better pregnancy outcomes, but this remains to be proven. To achieve this Kt/V target, therapy volume of up to 20 L per day has been recommended [16]. This approach is not practical in our case as besides doubling up the therapy cost incurred for dialysate, it will also require a PD continuous cycler machine.…”
Section: Discussionmentioning
confidence: 99%
“…A report by Gumus et al [5] explored the relationship between glomerular filtration rate and parity and found that pregnancyassociated hyperfiltration did not adversely affect kidney function in women with multiple pregnancies. A recent report by Smith and colleagues highlighted the utility of intensifying the peritoneal dialysis prescription to include 24-h continuous cycler peritoneal dialysis during the third trimester [6], and in the current issue, Tuot et al [7] present an interesting case of nutritional support provided to a pregnant woman on hemodialysis with hyperemesis gravidarum using intradialytic parenteral nutrition (IDPN). The latter two reports underscore the need for increased dialysis dose to mitigate the deleterious effects of the uremic milieu on the developing fetus, a practice that is in agreement with expert opinion [8][9][10].…”
mentioning
confidence: 98%